Development of Creative Music–Based Instructional Materials for Traditional Patrol Music - Jarmani, Jarmani (PT. Hafasy Dwi Nawasena, 2026)
Traditional patrol music is a form of folk music that has developed within communities in East Java and holds significant cultural, social, and educational value. However, in elementary music education, patrol music has not been optimally utilized as instructional material that encourages students’ creativity. Learning practices tend to be reproductive and focus on imitation of traditional forms. This study aims to develop creative music–based instructional materials for traditional patrol music to enhance students’ engagement, creativity, and musical understanding. The research employed a research and development approach conducted with elementary school students of SDN Babatan IV Surabaya as the research subjects. The development stages included needs analysis, instructional design, material development, and validation. The results indicate that creative music–based instructional materials enable students of SDN Babatan IV Surabaya to actively explore rhythm, sound, and collaborative music-making, transforming patrol music into a contextual, participatory, and adaptive learning medium. This approach also contributes to the dynamic preservation of traditional music through meaningful learning experiences at the elementary school level